2-(3-Chloroanilino)pyridine - Fairuz, Zainal Abidin (International Union of Crystallography, 2009)
In the title compound, C(11)H(9)ClN, the dihedral angle between the aromatic ring planes is 44.2 (1)° and the bridging C—N—C bond angle is 127.60 (19)°. The amino N—H grouping makes a hydrogen bond to the pyridyl N atom of an adjacent molecule across a center of inversion, generating a hydrogen-bonded dimer.